2001
DOI: 10.1046/j.1445-2197.2001.02215.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐discharge surgical wound infection surveillance in a provincial hospital: Follow‐up rates, validity of data and review of the literature

Abstract: An effective post-discharge follow-up programme significantly increased the SSI rate. From the authors' experience and a literature survey, possible ways to achieve high follow-up rates were suggested. It was also recommended that professional and regulating bodies in Australia be encouraged to standardize methodology and set minimum follow-up rates for post-discharge SSI surveillance. Increasing use of computerized hospital database systems for automated data gathering and processing should make this more pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 42 publications
1
22
0
6
Order By: Relevance
“…Which of our fi ndings may be valid for other hospitals? First, approximately two-thirds of the SSIs were identifi ed after discharge, which is a noteworthy fi nding and is in agreement with other reports 5,[8][9][10] . In addition, the proportion of PD-SSI varied among specialties, another fi nding that has been previously reported 11 .…”
supporting
confidence: 80%
“…Which of our fi ndings may be valid for other hospitals? First, approximately two-thirds of the SSIs were identifi ed after discharge, which is a noteworthy fi nding and is in agreement with other reports 5,[8][9][10] . In addition, the proportion of PD-SSI varied among specialties, another fi nding that has been previously reported 11 .…”
supporting
confidence: 80%
“…Considerando a tendência mundial em se reduzir cada vez mais a permanência hospitalar, as infecções de sítio cirúrgico extra-hospitalares dificilmente serão diagnosticadas caso não haja controle de egressos, uma vez que de 12% a 84% destas infecções manifestam-se após a alta do hospital 6,7,8,18,19,20 . No Brasil, entretanto, na maioria dos hospitais a vigilância das infecções de sítio cirúrgico é feita apenas durante a internação do paciente e é interrompida no momento da alta hospitalar 6,7 .…”
Section: Discussionunclassified
“…Apesar dos critérios para este tempo de seguimento e para a taxa de retorno dos pacientes não estarem bem definidos, a maioria dos autores preconiza trinta dias e um índice de acompanhamento maior que 80% 20 . Neste estudo, 98,6% dos pacientes da coorte foram acompanhados durante trinta dias.…”
Section: Discussionunclassified
“…The authors found a post-discharge infection rate of 8.38%, which is consistent with the findings of a review article that reported rates of 2-14%. [99] They also found strong statistical evidence that post-discharge surgical site infection (SSI) independently causes:…”
Section: Costs Incurred After Discharge Due To Surgical Site Infectionmentioning
confidence: 98%